STUDI DESKRIPTIF FAKTOR-FAKTOR RISIKO PENYEBAB OSTEOPOROSIS DI POSYANDU LANSIA SUGIH WARAS, MOJOSONGO, JEBRES, SURAKARTA - Suwarnisih suwarnisih; siskana Dewi Rosita (Viva Medika, 2018)
Related to the health aspect, biologically the elderly has experienced aging process, the antibody decreasing was signed by the more subject of the body to the attack of some diseases which leads to death. The older women got reproduction health problem when their fertile period is ended (menopause) (Pinem, 2009). The purpose of the research is to obtain the factors of the risk that caused osteoporosis in Sugih Waras Integrated Health Service for Elderly Mojosongo, Jebres, Surakarta. This was a descriptive observational research been done in Sugih Waras Integrated Health Service for Elderly Mojosongo, Jebres, Surakarta. The population of the research was all the women who came to Sugih Waras Integrated Health Service for Elderly. This used total sampling, and the respondents were 32 women. Frequency distribution was used as the data analysis. The result of the study shows that the respondent who has the risk of osteoporosis is 18 women (56%), and who does not have the risk of osteoporosis is 14 women (44%). The highest number of osteoporosis causing risk factors is 32 people of female gender (100%) and 32 people of Asian race (100%), the hormonal degree of the respondent who experienced menopause is 29 women (91%). The factors from the respondents’ life style is about 78%, food consuming and inherit factors is 59%, and factors of the women above 55 is 56%. The conclusion of the research is the respondent who has the risk of causing osteoporosis is 18 women (56%), and who does not have the risk of osteoporosis is 14 women (44%).